Harnessing live vectors for cancer vaccines: Advancing therapeutic immunotherapy - Chinmay T. Jani; Aysswarya Manoharan; Peter J. DeMaria; Marijo Bilusic (Human Vaccines & Immunotherapeutics)
Cancer vaccines represent a promising approach within immunotherapies. These vaccines are tailored to target tumor-specific antigens, thereby offering a precision approach to cancer treatment. The key principles in developing therapeutic cancer vaccines include identifying appropriate vaccine targets and selecting effective vaccine delivery platforms. These delivery platforms are diverse and have evolved to enhance the immune response. This review explores live cancer vaccines and the biological entities involved. Live cancer vaccines leverage the use of various biological entities to stimulate an immune response. These biological entities including bacterial, yeast-based and viral vectors, have unique properties that can be harnessed to target and destroy cancer cells while eliciting a robust immune response. Clinical trials of cancer vaccines are investigating standalone and combination treatment strategies in the prophylactic, adjuvant, and palliative settings. This review offers insights into the current oncologic vaccine landscape and potential future development.